PENGENALAN AKAD DAN PRODUK BANK SYARIAH PADA MASYARAKAT KAMPUNG KIARA PAYUNG, DESA CIASIHAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR. - Dewi Amalia; Tubagus Rifqy Thantawi; Azizah Mursyidah (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2021)
The purpose of this community service program is to increase a comprehensive and integrative understanding of the community and community leaders, especially the community in Kampung Kiara Payung Rw 08 Ciasihan Village, Pamijahan District, Bogor Regency regarding contracts and products in Islamic banking. The activity of disseminating sharia banking contracts and products in the community needs to be provided by the speaker to open the public's insight about Islamic banking. The result of this activity is the community, and the community leaders have knowledge about sharia banking contracts and products and have the desire to join as sharia banking customers around Bogor. Keywords: Dissemination, Akad, Product, Islamic Bank, Community Service.